Influence of Participatory Project Practices on Ruwasa Project’s Performance: The Case of Ushetu District, Tanzania - Ndabavunye , Cyprian; Ndolage, Dionis J. (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2025)
The study investigated the influence of participatory project practices (PPP) on performance of rural water projects carried out by Rural Water Supply and Sanitation Agency (RUWASA) in Ushetu district, Tanzania. It specifically looked at the influence of participatory project planning and implementation, monitoring, and communication on project performance. Using a casual research design and a Likert rated questionnaire, the study collected quantitative primary data from 171 respondents, including 143 water users and 28 RUWASA staff. Both descriptive and inferential statistics such as Pearson correlation and multiple linear regression were used to analyse the data. The results showed a positive relationship between project performance and participatory project planning, implementation, monitoring, and communication. The multiple linear regression analysis revealed that participatory project planning and implementation had a significant positive impact on project performance. Similarly, a participatory project monitoring and communication were also found to have a positive effect on project performance. The study concluded that involving the community in project planning, implementation, monitoring, and communication can enhance the performance of RUWASA projects in terms of cost-effectiveness and sustainable clean water supply. It was recommended that community members participate in all aspects of project planning, implementation, and monitoring, and that participatory communication be prioritized to facilitate knowledge-sharing and informed decision-making.